Association Between Breastfeeding and Child Stunting in Mexico - Ana Paola Campos; Mireya Vilar-Compte; Summer Sherburne Hawkins (Ubiquity Press, 2020)
Background: Globally, the prevalence of child stunting has been decreasing over the past decades. However, in low- and middle-income countries such as Mexico, stunting is still the most prevalent form of undernutrition affecting a large number of children in the most vulnerable conditions. Breastfeeding has been identified as one of the key affordable and modifiable maternal health behaviors protecting against child stunting. Objective: To examine the association between breastfeeding (defined as never breastfed, any breastfeeding for <6 months, and any breastfeeding for ≥6 months) and other individual-, household-, and area-level factors with child stunting (defined as length/height-for-age-z-score for sex under -2 standard deviations of the World Health Organization child growth standards' median) in Mexico. Methods: Secondary data analysis using the 2012 Mexican Health and Nutrition Survey, which allowed representativeness of rural and urban areas at national level and among 4 regions in Mexico. Our subset included data on 2,089 singleton Mexican children aged 6-35 months with information on previously identified risk and protective factors for stunting. We conducted fixed- and mixed-effects logistic regression models sequentially controlling for each level of factors. Findings: Overall, 12.3% of children were stunted and 71.1% were breastfed for ≥6 months. Any breastfeeding and being female were consistent protective factors against child stunting across all models. In contrast, child low birthweight, maternal short stature, higher number of children aged <5 years per household, and moderate to severe food insecurity were consistent risk factors for child stunting across all models. Conclusions: According to our findings, efforts to reduce child stunting in Mexico should include prenatal strategies aiming to prevent low birthweight offspring particularly among short-stature women, moderate to severe food insecure households, families with a higher number of children aged <5 years, and indigenous communities. Postnatal components should include multilevel strategies to support breastfeeding.